Dental discoloration caused by Grey-MTAFlow cement: analysis of its physicochemical, biological and antimicrobial properties - Pelepenko, Lauter Eston; Saavedra, Flavia; Bombarda, Gabriela Fernanda; Figueiredo de Almeida Gomes, Brenda Paula; de-Jesus-Soares, Adriana; Zaia, Alexandre Augusto; Hungaro Duarte, Marco Antonio; Tanomaru-Filho, Mario [UNESP]; Marciano, Marina Angelica (Univ Sao Paulo Fac Odontologia Bauru, 2020)
Tricalcium silicate-based cement are materials used in reparative and regenerative procedures in endodontics. A recently proposed formulation aimed to enhance handling during clinical use with a versatile material applicable by syringe. Although, the use of bismuth oxide as radiopacifier and grey raw powder are drawbacks considering aesthetics. Objectives: Evaluate physicochemical, biological, and antimicrobial properties of Grey-MTAFlow (Ultradent) and assess whether the addition of zinc oxide (ZnO) prevents dentinal discoloration caused by bismuth oxide. Methodology: Grey-MTAFlow was manipulated in 'thin' consistency for all tests. Luminosity, color change, ion migration to dentine, radiopacity, setting time, ISO 6876:2012 linear flow, volumetric lateral flow and central filling of simulated grooves scanned using micro-computed tomography (pCT), pH, calcium release, volumetric change using pCT, chemical characterisation, cytotoxicity, and antimicrobial activity were assessed. Addition of 5% ZnO to Grey-MTAFlow and a bismuth-containing experimental composition were comparatively tested. Statistical analyses used Shapiro-Wilk, T-test, ANOVA, and Kolmogorov-Smirnov (p<0.05). Results: The addition of ZnO to Grey-MTAFlow prevented dentine darkening after 90 days due to bismuth migration reduction, although no statistical difference was found (p=0.863). ZnO addition significantly enhanced Grey-MTAFlow radiopacity without differences in initial setting time. Grey-MTAFlow presented an ISO linear flow of 10.9 mm and a balanced volumetric lateral flow with central filling in pCT evaluation. All compositions presented an alkaline pH after immersion. Grey-MTAFlow had a significantly higher calcium ion release after 28 days in comparison to 24 hours (p=0.011) and volumetric expansion of 0.4 +/- 1.8% after immersion. ZnO addition altered the hydrated cement matrix once calcium hydroxide (portlandite) could not be detected in characterisation. Neither of the materials produced inhibition halos nor reduced bacterial turbidity, but all presented cytocompatibility above 100%. Conclusion: Grey-MTAFlow expanded after immersion and exhibited higher luminosity values after the evaluation period when ZnO was added, but chemical modifications after this addition occurred.
Keywords: Tooth discoloration; Dental materials; Bismuth; Zinc oxide